MARGINALISASI AGAMA DAN ETNIS TIONGHOA DALAM RIWAYAT NEGERI YANG HARU - Rohman, Hudha Abdul (Balai Bahasa Jawa Tengah, 2018)
This paper?discusses how?these forms of?marginalization?that is done?the new order?government (Orde Baru) which?displayed in the?collection of?elected Kompas short stories in?the 1981-1990 Riwayat Negeri yang Haru.?A collection of?short stories?written?by?55?authors and?published?in?2006.?This paper?uses?the theory of?marginalization by?Alcock?(1993) and the?approach of the?new?historicism?of Stephen?Grenblatt.?The results of?this paper?found that the elected Kompas short story in?1981-1990?represent?situations and?social?conditions of the?new order government?which?marginalize?people and minority groups from?various aspects?such as economic,?social, political,?and religious.?Marginalization?against? depicted?through various?social phenomena?associated?marginalization of?women, the?centralization?of power,?religion, and?ethnic Chinese.Keywords: marginalization, Orde Baru, short story, Kompas, new historicism